Memories of Halyna Tishchenko, Founder of the Department of Fabric and Clothing Design at the Kharkiv State Academy of Design and Arts - Omelchenko, Olga (HUDPROM: The Ukrainian Art and Design Journal, 2025)
For the historical memory of any higher educational institution and its specific structural unit, it is vital to preserve not only official archival records about the history of its emergence and development but also recollections of the people who shaped its development, especially if they were outstanding personalities. Formal documents, often dry and bureaucratic in tone, cannot fully convey the atmosphere of the early years, the spirit of innovation, or the personalities who stood at the origins of a new discipline. By contrast, artefacts, artistic projects, and especially personal memories allow us to glimpse the living history behind institutional foundations. The presented material arose from the need to preserve for the future generations the memory of those who established textile and clothing design as a distinct educational school at the Kharkiv State Academy of Design and Arts (KSADA) – the first of its kind in Ukraine. At the centre of this history stands Halyna Tishchenko (July 1, 1936 – May 12, 2025), founder and first head of the Department of Artistic Textiles at KSADA. A well-known Kharkiv artist of monumental and decorative-applied art, a master of tapestry, and an inspiring teacher, she dedicated her life to nurturing this field. The author of the article conveys her impressions, full of gratitude and admiration, of the creative fate and personality of her teacher, and later her colleague, H. Tishchenko, her artistic achievements of one of the leading professors of the old art school of KSADA, who devoted a large part of her creative life to the formation of the field of artistic textiles and clothing as an educational direction at the Academy. Special attention is given to her partnership with her husband, Professor O. Pronin (1934–2002), founder of the Kharkiv school of artistic stained glass, with whom she shared both a creative and life journey.